Immunogenicity Assessment of Rift Valley Fever Virus Virus-Like Particles in BALB/c Mice - Li, Yuetao; Han, Li; Zhao, Yongkun; Zheng, Xuexing; Wang, Hualei; Gai, Weiwei; Jin, Hongli; Li, Guohua; Wang, Qi; Feng, Na; Gao, Yuwei; Yang, Songtao; et al. (Frontiers in Veterinary Science, 2020)
Rift Valley fever (RVF) is an acute, febrile zoonotic disease that is caused by the RVF virus (RVFV) and is spread by arthropod vectors. Virus-like particle (VLP) vaccines, which have the advantages of strong immunogenicity and safety, play an important role in the prevention of this disease. VLPs for RVFV were successfully prepared by our research group using a baculovirus-insect cell expression system. To study the immunogenicity of these RVFV VLPs, a correct 3rd or 4th generation recombinant baculovirus, rBac-NG, was identified and used to infect Sf9 cells, which were cultured in suspension at a large scale. Subsequently, cell debris was removed by centrifugation, and the VLPs were concentrated by ultracentrifugation and purified using a sucrose gradient, after which they were used to immunize BALB/c mice by intramuscular injection. The results showed that the RVFV VLPs prepared by our research group could effectively induce mice to produce RVFV neutralizing antibodies and that the prepared VLPs could stimulate mouse spleen cells to produce high levels of the cytokines IL-4 and IFN-γ. Moreover, the proportion of lymphocytes producing IL-4 and IFN-γ in the spleen of mice immunized with RVFV VLPs was significantly increased. Therefore, the RVFV VLPs prepared in this study had strong immunogenicity and could effectively activate humoral and cellular immunity in mice. This study lays a solid foundation for the development of RVFV VLP vaccine candidates and promotes the healthy development of animal husbandry.